Hubungan dukungan suami dengan tingkat nyeri persalinan pada ibu bersalin kala I - Rohani Mustari; Herlianty Herlianty; Junika Battung (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Ikatan Dokter Indonesia (IDI), 2026)
Background: Childbirth is a physiological process often accompanied by severe pain, especially during the first stage of labor. The level of pain experienced by mothers is influenced by various factors, one of which is their husband's support. The presence and involvement of a husband during labor is believed to help reduce pain perception and increase maternal comfort. Purpose: To determine the relationship between husband's support and the level of labor pain among mothers giving birth. Method: A cross-sectional design with a sample size of 45 respondents selected using purposive sampling. The instruments used were a 7-item Husband's Support Questionnaire and a Visual Analog Scale (VAS) to measure labor pain levels. Data were analyzed using a chi-square test with a significance level of p <0.005. Results: The majority of respondents received low levels of husband's support (62.2%), while 37.8% received high levels of support. The majority of respondents experienced moderate levels of labor pain (57.8%), followed by mild pain (26.7%), and severe pain (15.6%). Correlation: Statistical results indicate a significant relationship between husband's support and labor pain levels. High levels of husband's support play a significant role in helping mothers reduce their perception of pain during labor. Keywords: First Stage of Labor; Husband's Support; Labor Pain. Pendahuluan: Persalinan merupakan proses fisiologi yang sering disertai dengan neyri hebat, terutama pada kala I persalinan. Tingkat nyeri yang dialami ibu dipengaruhi oleh berbagai factor, salah satunya adalah dukungan suami. Kehadiran dan keterlibatan suami selama persalian diyakini dapat membantu mengurangi persepsi nyeri dan meningkatkan kenyamanan ibu. Tujuan: Untuk mengetahui hubungan antara dukungan suami dengan tingkat nyeri persalinan pada ibu bersalin. Metode: Desing Cross Sectional Dengan Jumlah sampel 45 responden yang dipilih secara purposive sampling, instrument berupa kueisioner Dukungan suami 7 item dan visual Analog Scale (VAS) untuk mengukur Tingkat nyeri persalinan. Data dianalisis dengan menggunakan ujia chi-square dengan Tingkat signifikansi p <0.005. Hasil: Sebagian besar responden memperoleh dukungan suami rendah (62.2%), sedangkan yang memperoleh Dungan tinggi sebesar 37.8%. Tingkat nyeri persalinan yang dialami responden Sebagian besar berada pada kategori sedang 57.8%, diikuti nyeri ringan 26.7%, dan nyeri berat 15.6%. Simpulan: Hasil uji statistik menunjukkan bahwa terdapat hubungan yang bermakna antara dukungan suami dengan tingkat nyeri persalinan. Dukungan suami yang tinggi berperan penting dalam membanti ibu mengurangi persepsi nyeri selama proses persalinan. Kata Kunci: Dukungan Suami; Kala I Persalinan; Nyeri Persalinan.